Uso eficiente de agua de riego en arroz - Perú - Muñoz, Luis Armando; Romero Sánchez, Miguel Antonio; Sierra, Leidi (Bioversity International and the International Center for Tropical Agriculture, 2020)
This document is intended to serve as policy guidance for the agricultural sector, specifically for the use of water in irrigated rice in Peru, the information presented was obtained from data capture with sensors and data analysis. The document has been received and accepted by the Ministry of Agriculture and Irrigation of this Country.